Mechanism of Innate Immune Responses Against SARS-COV-2 Infection - Hiwa Abdulrahman Ahmad; Khalat Karwan Fares (Zanco Journal of Pure and Applied Sciences, 2023)
The immunopathogenesis of the Coronaviruses (CoVs) is still under study. The innate immunity components can differentiate self and non-self-antigens, be involved in viral particle recognition, and restrict viral replications through antiviral protein expressions. Induction of antiviral innate immune responses against CoV vastly depends on recognizing pathogen-associated molecular pattern molecules (PAMPs) by pattern recognition receptors (PRRs). PAMPs mount the activation of (Toll-Like Receptors) TLR cascade and initiate transcription factors, involving Nuclear Factor- κB (NF-Κb), Interferon Regulatory Factors (IRF3), and (IRF7), and this results in the synthesize of Interferons (IFN) type Ⅰ. Subsequently, type Ⅰ IFN inhibit viral replications, regulate and modulate the immune system. Dendritic cells (DCs) reside in the respiratory tracts. They can recognize viral particles via TLR and initiate innate and adaptive immunity and repress viral spreads through IFNs production. Impairment of TLR, impediment of IFN expression, and/or disresponse of innate immune responses may be associated with tissue destruction after viral elimination. Here, emerging the reviews knowledge on the mechanism of non-specific immune responses against SARS-COV-2.